A modality-specific somatosensory evoked potential test protocol for clinical evaluation: A feasibility study. Issue 12 (December 2021) - Fabig, Sophie-Charlotte; Kersebaum, Dilara; Lassen, Josephine; Sendel, Manon; Jendral, Swantje; Muntean, Alexandra; Baron, Ralf; Hüllemann, Philipp
Highlights: We present a pilot neurophysiological test protocol for the somatosensory system. Specific fiber subtypes are assessed by their respective modality-specific test. The protocol's applicability is demonstrated in three polyneuropathy patients. Abstract: Objective: We aimed to establish an objective neurophysiological test protocol that can be used to assess the somatosensory nervous system. Methods: In order to assess most fiber subtypes of the somatosensory nervous system, repetitive stimuli of seven different modalities (touch, vibration, pinprick, cold, contact heat, laser, and warmth) were synchronized with the electroencephalogram (EEG) and applied on the cheek and dorsum of the hand and dorsum of the foot in 21 healthy subjects and three polyneuropathy (PNP) patients. Latencies and amplitudes of the modalities were assessed and compared. Patients received quantitative sensory testing (QST) as reference. Results: We found reproducible evoked potentials recordings for touch, vibration, pinprick, contact-heat, and laser stimuli. The recording of warm-evoked potentials was challenging in young healthy subjects and not applicable in patients. Latencies were shortest within Aβ-fiber-mediated signals and longest within C-fibers. The test protocol detected function loss within the Aβ-fiber and Aδ-fiber-range in PNP patients. This function loss corresponded with QST findings. Conclusion: In this pilot study, we developed a neurophysiological test protocol that can specifically assess most of the somatosensory modalities. Despite technical challenges, initial patient data appear promising regarding a possible future clinical application. Significance: Established and custom-made stimulators were combined to assess different fiber subtypes of the somatosensory nervous system using modality-specific evoked potentials.